Konflik dan Kelas Sosial dalam Novel Ketika Cinta Harus Bersabar Karya Nurlaila Zahra - Nensilianti, Nensilianti; Ahmadi, Hayana; Ridwan, Ridwan (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2023)
Genetic Structuralism Analysis is used in this study to discuss human facts, collective subjects, and worldviews in the novel When Love Must Be Patient by Nurlaila Zahra. Through a genetic structuralism approach, this study identifies and analyzes the narrative structure that emerges from social, cultural, and historical factors that shape the facts of humanity in the novel. Apart from that, this study also explores how the collective subject is influenced by these factors and how the world view contained in the novel is reflected through the resulting narrative structure. The results of the research show that the historical, social, and cultural factors that occurred during the writing of the novel greatly influenced the structure and meaning of the novel When Love Must Be Patient. This novel displays different world views through the characters that represent them, such as views on love, religion, culture, and gender. In addition, this novel also shows the complexity of collective subjects in society, such as the tension between traditional and modern values, as well as the role of the individual in maintaining the integrity and harmony of society.